PEMBERDAYAAN MASYARAKAT PADA PENGEMBANGAN USAHA RUMAH PEMOTONGAN HEWAN MAKASSAR - Murbayani Murbayani; Fina Diana; Rasdiah Rasyid (BERKEMAJUAN : JURNAL PENGABDIAN PADA MASYARAKAT, 2017)
The demand for meat has increased as population growth and changes in community style and patterns of consumption. Similarly, the people of Makassar, known as a beef and buffalo commsumen for barbagai dishes and local culinary. The need for meat in Makassar City is predicted to require as many as 553 heads per day to supply the meat in Makassar. One of the regional companies given the authority to serve the meat needs is PD. Animal Cutting House (RPH). IbM activities that we will do is the management training of Cutting House management on PD managers. RPH Kota Makassar, socialization and stimulant to beef entrepreneurs, establishment of small and medium business group as business development partner of RPH Kota Makassar as well as training of RPH (meat, skin, bone and cattle urine) RPH business development for community group of SME actors who have formed it. The objective of each activity is to increase the knowledge of the slaughterhouse management related to RPH management so that it can meet the established standards, the awareness of the breeders and cattle and buffalo traders around Makassar City to legally slaughter animals in PD. RPH so that they actively produce and supply cattle and buffalo to RPH, as well as the formation of knowledgeable and skilled group of people in producing processed meats, and the utilization of cattle waste (skin, bone and urine) so as to have the opportunity to partner in PD business development. RPH. Overall, the ultimate goal of IbM's activities is the increasing income of PD. RPH so as to support increasing regional income and sustaining the economy of small to medium-sized communities.